Magnetic Susceptibility of nanoparticles in the Lubuk Basung Region - Janna, Anisa; Hamdi, Hamdi; Amir, Harman; Zulhendra, Zulhendra (Department of Physics, Universitas Negeri Padang, 2024)
Nanoparticles is particles that have size very small, generally in range from 1 to 100 nanometers. Nanoparticles have one​ uniqueness with exists characteristic superparamagnetic. Characteristic superparamagnetic is properties the material has magnetization tall if given external magnetic field, however when No There is external magnetic field mark the average magnetization is zero. On size certain, nanoparticles can show transition from superparamagnetic to ferromagnetic or antiferromagnetic. Influence size grain and structure crystal to characteristic magnetic is one​ method in determine susceptibility. Susceptibility magnetic is defining constant​ big small a material to magnetized. Study This aim to the analyze mark susceptibility magnetic from nanoparticles rock floating in the area Lubuk Basung. Method used​ is method magnetism rock with tool Bartington Magnetic Susceptibility Meter Type B. Research results shows in the area Lubuk Basung LBS 23-02 and LBS 23-03 are available concentration content high Fe element and concentration content element Ti more low. Magnetic susceptibility in the area Lubuk Basung have characteristic antiferromagnetic magnetism, and has type grain almost no There is details superparamagnetic and also has mixture superparamagnetic and granular rough or details superparamagnetic <0.05 μm equivalent with <50 nm. So that depicted that size nanoparticles contained in the sample rock floating LBS 23-02 and LBS 23-03 have size nanoparticles below 50 nanometers with characteristic antiferromagnetic magnetism.